Сравнительное исследование коррозии стоматологического (900°) и ювелирного (585°) золота в среде полости рта - Лавренко, В.А.; Лось, В.В.; Малышевская, А.И.; Швец, В.А.; Талаш, В.Н.; Кузнецова, Л.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The corrosion behavior of tooth and jewellery gold alloys in the medium of a mouth cavity under the extreme situations of a possible contact with other metal or an inhomogeneous crown region has been simulated using the polarization from the outer current source. The methods of potential-dynamic polarization curves, layer-by-layer Auger electron spectroscopy analysis, as well as XRD and petrographic analyses of reaction products, have been used. It has been established that the tooth gold (900°) being the Au3Cu intermetallide is not practically subjected to corrosion at all, whereas the jewellery gold (585°) being the mixture of AuCu3 and AuCu intermetallides with 6% Ag forms ~ 2μm corrosion film consisting of AgCl deposit with small Cu2O and CuO additives on its surface. The reason of such behavior of gold alloys consists in different crystal-chemical features of the structure of appropriate intermetallides, as well as in the different types of oxygen adsorption on their surface.